A Comprehensive Review of Scientific Literature on Methods for Determining Discount Rates in Corporate Practices - Klára Szűcs Markovics (Theory, Methodology, Practice, 2012)
On the basis of the findings of research conducted in eighteen countries and in the Central and Eastern European region, this study seeks to understand how the discount rate is set when capital budgeting practices are involved. According to the reviewed academic literature, the weighted average cost of capital is the most popular method of determining discount rates in a number of countries. Besides this, decision makers often apply the single method of corporate required rate of return regardless of the character of specific decision aspects and market risks.